2011
DOI: 10.1111/j.1600-0633.2011.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg size and its relationship with fecundity, newborn length and female size in Cuban poeciliid fishes (Teleostei: Cyprinodontiformes)

Abstract: This study describes the relationship between egg size (ES) and brood size (BS), newborn length (NL) and female total length (FTL) in ten species of Cuban poeciliids. Variability and the level of association among variables are analysed and comparisons of ES among species established. Egg size has the lowest variability among the analysed variables and in most species is not correlated with BS, when the effect of FTL is controlled. Cuban poeciliids, thought to be primarily lecithotrophic, can be separated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 41 publications
6
25
0
Order By: Relevance
“…The strong positive relationship between egg size and larval length is consistent with numerous studies across a range of freshwater genera (Marsh 1986;Miller et al 1988;Einum 2003;Ponce de Le on et al 2011) and confirms the ecological relevance of the oocyte differences reported by Jones et al (in press). Differences were greatest between the headwater species (G. eldoni and G. pullus) and the lower catchment species (G. anomalus) with mean interspecific differences in total length at hatch as large as 2.6 mm or 41%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The strong positive relationship between egg size and larval length is consistent with numerous studies across a range of freshwater genera (Marsh 1986;Miller et al 1988;Einum 2003;Ponce de Le on et al 2011) and confirms the ecological relevance of the oocyte differences reported by Jones et al (in press). Differences were greatest between the headwater species (G. eldoni and G. pullus) and the lower catchment species (G. anomalus) with mean interspecific differences in total length at hatch as large as 2.6 mm or 41%.…”
Section: Discussionsupporting
confidence: 90%
“…Differences in early life-history traits can also have unpredictable consequences for how species respond to anthropogenic pressures (e.g. Such substantial differences in maternal investment strategies are likely to have marked consequences for the early ontogeny (Bagenal 1969;Miller et al 1988;Ponce de Le on et al 2011). Thus, the lack of information regarding the morphology and behaviour of stream fish during the larval period represents a major knowledge gap in freshwater fish ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Cabrera et al (2008) found that the number of embryos increased with female's size. This pattern coincides with that proposed by other authors for several species within the family Poeciliidae (Downhower et al, 2000;Reznick et al 2007; Ponce de León et al, 2011León et al, , 2013Zuñiga-Vega et al, 2011). On the other hand, Vargas & Sostoa (1996) stated that the fecundity peak of the species G. holbrooki Girard, 1859 occurs in July when females are bigger.…”
supporting
confidence: 90%
“…It needs to be noted, however, that egg size may also play a role since individuals with the same GSI but different egg sizes can produce different numbers of offspring. Such relationships between fecundity, egg size and juvenile performance are well known in many fish species [66], however, there is no clear association between egg size and maximum body length of newborn gobiids [67]. Males had a similar reproductive power along the invasion pathway (constant by time), while fecundity of females increased over time since invasion.…”
Section: Discussionmentioning
confidence: 99%